TOWARDS PLAY-BASED LEARNING PRACTICE - Mulia, Dewi (Kajian Linguistik dan Sastra, 2016)
This paper provides the rationale for an overview and a discussion of theÂ issues that affect best practices for play-based learning, particularly the implicationsof adultsâ attitudes regarding childâs play and learning for play-basedÂ learning practice in early childhood educational settings in Indonesia. The conceptof play-based learning can be attributed to the National Early Years LearningÂ Framework in Indonesia. However, the practice remains challenging as theÂ result of diverse concepts of childâs play and learning. This discussion beginsÂ with an overview of the framework and of government support. It details theÂ relevant research on the challenges that educators and teachers have faced withÂ the implementation of the framework.